Stressors and academic performance among part-time students in a public university in Malaysia / Siti Rapidah Omar Ali ... [et al.] - Omar Ali, Siti Rapidah; Ajit, Nurulain; Mohd Said, Nur Shafini; Mat, Khalid Amin; Abdullah, Nasiha (Universiti Teknologi MARA, Kedah, 2021)
Stress can be considered as a universal phenomenon. It can affect all levels of students and grades. The objective of the study was to investigate the association between factors that influence stress namely workload, academic stress, and financial stress and students' academic performance. A group of 357 e-pjj students in a public university have participated in this study. Data were analyzed using Statistical Package for Social Scien ce (SPSS) version 23. Information on demographic background, workload, academic stress, financial stress, and academic performance were collected. Correlation and multiple regression analyses were also examined. The findings indicated that, there is a moderate relationship between independent and dependent variables. Financial stress is proven to be the most significant factor towards academic performance.